Maternal Hyperthyroidism and Delayed Diagnosis of Bilateral Choanal Atresia in a 4-Month-Old Infant: A Case Report on Stentless Endoscopic Reconstruction - Meilia Ghinasari; Bestari Jaka Budiman; Dolly Irfandy (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Bilateral choanal atresia (BCA) is a life-threatening congenital anomaly typically presenting as a neonatal respiratory emergency. Survival beyond the neonatal period without surgical intervention is exceptionally rare. While the etiology is multifactorial, emerging evidence implicates maternal thyroid dysregulation in craniofacial malformations. This study reports a rare case of BCA diagnosed in a 4-month-old infant and evaluates the efficacy of stentless endoscopic repair using laterally-based mucoperiosteal flaps. Case presentation: A 4-month-old female infant presented with failure to thrive (weight 5.2 kg, less than the 3rd percentile) and cyclical respiratory distress. Perinatal history revealed the mother had Graves' disease and discontinued methimazole at 6 weeks gestation. Retrospective analysis of maternal serum indicated uncontrolled thyrotoxicosis during the critical organogenesis window (TSH less than 0.01 mIU/L; fT4 2.8 ng/dL at 7 weeks). Diagnostic imaging confirmed mixed bony-membranous atresia. The patient underwent transnasal endoscopic choanoplasty using a laterally-based mucosal preservation technique. A 10-Fr silicone feeding tube was placed transnasally but did not function as a structural stent. Conclusion: The intervention resulted in immediate airway patency. Quantitative outcomes showed an increase in oxygen saturation from 96% to 99% on room air and significant weight gain from 5.2 kg to 6.7 kg over two months. Follow-up at six months showed no restenosis. This case suggests a potential dual-hit teratogenic mechanism involving early methimazole exposure and subsequent uncontrolled maternal hyperthyroidism. Furthermore, it supports the efficacy of stentless repair in minimizing granulation tissue formation.